Analysis and Testing of Lubricating Oils in Mine and Mill Production Equipment - R. A. Ford (Canadian Institute of Mining, Metallurgy and Petroleum, 1977)
The paper outlines: methods used for the determination of wear metals in motor and transmission oils; contaminents in motor, transmission and crusher lubricating oils; and viscosity determinations. Case histories and costs are presented to illustrate the value of an oil analysis program. Introduction NORANDA MINES LIMITED (BELL COPPER DIVISION) is located on the shores of Babine Lake, approximately 450 miles north of Vancouver, British Columbia. Access to the mine is by road from Topley, B.C., about 40 miles away. When a preventive maintenance analysis program was first considered, it was obvious that if samples were to be sent out for analysis, results would not be available for at least a week, due to the distance from any commercial laboratory. The assay laboratory was asked to investigate the possibility of determining wear metals on site. A limited program was started soon after production commenced, and this has now grown to include all large mobile equipment as well as crushers and grinding mills. The laboratory also now determines viscosity, fuel dilution, dirt and abrasives, glycol and water. All these results are ready within two days. This paper will outline the methods used, data interpretation, several case histories and the benefits from such a program.